Determinants of Capital Adequacy and Liquidity Risk on Profitability in the Banking Sector - Saputri, Oktaviana, Dewi; Edward, Mohammad Yunies (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study aims to analyze the impact of capital adequacy and liquidity risk on the profitability of banks listed on the Indonesia Stock Exchange in 2019-2023.  Methodology: Using a quantitative approach, panel data regression analysis was performed on a sample of 43 banks whose financial data was processed using STATA 17. Results: These results underscore the importance of effective capital management and liquidity strategies to optimize bank profitability. Findings: This study found that Capital Adequacy Ratio (CAR) does not significantly affect Return on Assets (ROA) but significantly affects Net Interest Margin (NIM). Meanwhile, Liquidity Risk (LDR) significantly and positively affects both profitability indicators (ROA and NIM). Novelty: Unlike previous studies, this research highlights the differential impact of capital adequacy on profitability indicators, offering a different perspective on banking performance. Originality: This study contributes by using the latest financial data (2019-2023) and examining ROA and NIM as profitability indicators. Conclusion: The findings indicate that liquidity risk management is crucial for improving profitability, while capital adequacy impacts bank performance depending on the profitability indicator used. Type of Paper: Empirical Research Article.